Asymptomatic Deep Vein Thrombosis in a Patient with Major Depressive Disorder - Ishida, Takuto (Hindawi Publishing Corporation, 2012)
Pulmonary embolism is a serious, life-threatening condition and most commonly derives from deep vein thrombosis of the lower extremities. Once deep vein thrombosis (DVT) reaches a proximal vein (i.e., popliteal vein or higher), pulmonary embolism reportedly occurs in up to 50% of patients. Case Presentation. We report on an inpatient with major depressive disorder in a catatonic state in whom an asymptomatic proximal deep vein thrombosis of 11 × 70 mm was detected through routine screening, using doppler ultrasound scanning. Anticoagulant therapy was immediately started and continued for three months, which resulted in resolution of the deep vein thrombosis. Discussion. To our knowledge, this is the first description of asymptomatic proximal DVT that was detected in a psychiatric inpatient setting. In light of the reported causal relationship between DVT and pulmonary embolism, screening for DVT can be of high clinical value in patients with psychiatric disorders, especially when their physical activity is highly compromised.